2021
DOI: 10.3390/app11135866
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Environmental Quality towards Classrooms’ Comforts Level: Case Study at Malaysian Secondary School Building

Abstract: The indoor environmental aspects of classrooms in secondary school buildings need to be determined to ensure that they meet the users’ basic requirements. Students’ efficiency and learning productivity can be affected if the classroom’s indoor environment is of poor quality. The question raised here: how can we ensure that the comfort level provided to building users in terms of indoor aspects is up to their satisfaction? Post Occupancy Evaluation (POE) is an instrument to examine the success of building desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The indoor environmental quality (IEQ) and indoor thermal environment of university buildings can affect students' physical health, mental health and learning efficiency (Zhang and Bluyssen, 2019;Li et al, 2021;Guevara et al, 2021;Norazman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indoor environmental quality (IEQ) and indoor thermal environment of university buildings can affect students' physical health, mental health and learning efficiency (Zhang and Bluyssen, 2019;Li et al, 2021;Guevara et al, 2021;Norazman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In general, school buildings are not thermally comfortable. Thus, classrooms must be designed accurately, more so in terms of facilities such as lighting and ventilation (Norazman et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the indoor environmental quality (IEQ) of the classroom is significant to be preserved. Besides that, thermal comfort conditions in educational buildings also encouraged student productiveness during the teaching and learning process [4]. Many researchers have studied the effect of environmental conditions on student performance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that natural ventilation can greatly reduce the amount of energy used and can save up to 25% of overall building energy consumption compared to a mechanical ventilated building [1], while Zhao et al, [2] reported about 40% of building energy consumption is compensated to mechanical ventilation and 35% of carbon dioxide emission in Europe country. The physical environment and thermal comfort level in a classroom could significantly influence the performance of students in terms of their motivation to study as well as their concentration during classes [3,4]. In relation to this, natural ventilation is attained by purposely built openings around the enclosure, or recently, the wind-assisting device is often applied to facilitate the process [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%